Age-dependent cortical overconnectivity in Shank3 mice is reversed by anesthesia - Elena Montagni; Manuel Ambrosone; Alessandra Martello; Lorenzo Curti; Federica Polverini; Laura Baroncelli; Guido Mannaioni; Francesco Saverio Pavone; Alessio Masi; Anna Letizia Allegra Mascaro (Translational Psychiatry)
Abstract Growing evidence points to brain network dysfunction as a central neurobiological basis for autism spectrum disorders (ASDs). As a result, studies on Functional Connectivity (FC) have become pivotal for understanding the large-scale network alterations associated with ASD. Despite ASD being a neurodevelopmental disorder, and FC being significantly influenced by the brain state, existing FC studies in mouse models predominantly focus on adult subjects under anesthesia. The differential impact of anesthesia and age on cortical functional networks in ASD subjects remains unexplored. To fill this gap, we conducted a longitudinal evaluation of FC across three brain states and three ages in the Shank3b mouse model of autism. We utilized wide-field calcium imaging to monitor cortical activity in Shank3b+/− and Shank3b+/+ mice from late development (P45) through adulthood (P90), and isoflurane anesthesia to manipulate the brain state. Our findings reveal that network hyperconnectivity, emerging from the barrel-field cortices during the juvenile stage, progressively expands to encompass the entire dorsal cortex in adult Shank3b+/− mice. Notably, the severity of FC imbalance is highly dependent on the brain state: global network alterations are more pronounced in the awake state and are strongly reduced under anesthesia. These results underscore the crucial role of anesthesia in detecting autism-related FC alterations and identify a significant network of early cortical dysfunction associated with autism. This network represents a potential target for non-invasive translational treatments.